J. R. R. Tolkien – A Literary Philosopher - Maria Filomena LOURO; Tânia AZEVEDO (Cultural Intertexts, 2015)
In several of his writings, J. R. R. Tolkien has openly talked about the sorrow he felt due to the fact that his homeland had no mythology of its own. Through his Middle-Earth imagery, he was able to create a cosmogony and dwell on the eternal fight between Good and Evil. However, it’s not in the mainstream texts on Middle-Earth that this intersection between literature and Philosophy is extensively explored. A definite answer will be found concerning the author’s main queries on how the land can be healed through the reader's encounter with an elf and a human philosopher and consequent engagement in their debate: Athrabeth Finrod ah Andreth (The Dialogue Between Finrod and Andreth). Through their ideas, fears, doubts and queries, we will understand that the healing of the marred earth has to come from within.